Analisis Pengaruh Promosi, Brand Ambassador, dan Persepsi Harga terhadap Keputusan Pembelian Melalui Minat Beli sebagai Variabel Mediasi: Studi Kasus Pembelian Revlon di E-Commerce - Naufal Afif Santoso; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2026)
This study was conducted to analyze the influence of promotion, brand ambassador, and price perception on purchase decisions with purchase intention as a mediating variable for Revlon products in e-commerce. The background of this research is based on the intense competition in the online cosmetics industry, which requires companies to implement appropriate marketing strategies to retain consumers. The data were obtained from a total of 140 respondents who had purchased Revlon products through marketplaces. The data collection was carried out using a questionnaire consisting of closed-ended questions on a 5-point Likert scale, which was distributed online. The analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software. The results show that promotion does not have a significant effect on purchase intention, while brand ambassador and price perception have a positive and significant effect on purchase intention. Furthermore, purchase intention does not have a significant effect on purchase decisions.